Perbandingan Metode Aritmatik, Metode Geometrik dan Metode Least Square pada Proyeksi Jumlah Penduduk - Indriyani, Indriyani; Rakhmawati, Fibri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to 1) Find out the application of these 3 methods and which method is the best in projecting the population in North Sumatra Province, 2) Find out the calculation results of the population in North Sumatra Province in the next 10 years using one of these 3 methods. The methods used are the arithmetic method, geometric method and least square method. The research results show that the least square method has the smallest standard deviation value, namely 525818.9095 compared to the arithmetic method which has a standard deviation value of 539847.056 and the geometric method which has a standard deviation value of 1571337.94. The conclusion is that the least squares method is used in calculating population projections in North Sumatra Province in 2023-2033 because it has the smallest standard deviation value and the results of population projections using the least squares method in 2023 are 15252306 and in 2033 are 16915092. Keyword : Arithmetic Method, Geometric Method And Least Square Method, North Sumatra Province.